Analisis Usaha Penggemukan Ternak Kambing dengan Pemberian Indigofera sp. dalam Ransum di Kabupaten Tasikmalaya : Feasibility Study of Goat Fattening with Indigofera sp. as a Diet in Tasiskmalaya - De Isal Sandiana; Kenedy Putra; Dyah Gandasari (Jurnal Agroekoteknologi dan Agribisnis, 2023)
Banjarwaringin Village in Salopa District, Tasikmalaya Regency has potential for goat farming as community farming. The study aims to examine the effect off Indigofera as a diet of sheep on body weight gain in Salopa District, Tasikmalaya. The method used was a completely randomized design method with 6 male goats as samples which were divided into 3 treatment groups and 2 replications. The design of the applied study that will be carried out is P0 with control, P1 with 1% Indigofera and P2 with 2% Indigofera. Business analysis using business analysis B/C ratio, R/C ratio, production BEP and price BEP. Sampling of body weight and the same age. The variables observed included PBHH of goats. F test with the SPSS version 15 analysis tool. The results showed that there was a significant difference in ADG P0 61.00 ± 2.828 (a), P1 101.00 ± 1.414 (c), P2 76.00 ± 5.567 (b). The results of the business analysis showed an increase in farmer's income of IDR 258,359 in the treatment with Indigofera, and the value of the R/C ratio was 1.09.